Fractal video compression - Lugue, Rachel Celeste S. (1999)
Still images and video presentations enhance the appearance and effectiveness of different applications. However using video and still images has its cost. Very large disk space is needed to store images especially scanned images; same with video files which consume a lot of space. Different compression methods are applied to still images and video to alleviate this problem, but none of the contemporary methods have explored the possibility of compressing the image through the use of self-similarity within the image. This paper deals with the use of a Fractal scheme in compressing still images and video. What the fractal scheme essentially does is to partition the images, get a portion of the image, compare it to other parts of the image, and determine the flips and the shifts in the RGB component intensities that would make the two portions similar. This scheme results in compression, since instead of individual pixel transformations (for a 24-bitmap this would mean 3 bytes per RGB component), flips and shifts are stored. This scheme has its advantages. It can achieve very high compression ratios if applied on an image with very high self-similarity. An image encoded using a fractal scheme can be decoded at any size. This leads to another benefit of the scheme which is better zooming capability. An ordinary bitmap when zoomed will show pixelization. A fractal encoded image can be enlarged without showing pixelization but will instead show artificially created detail.